Elderly pedestrians' self-regulation failures and crash involvement: The development of typologies. (December 2019) - Nakagawa, Yoshinori
Highlights: The cases of elderly pedestrian collisions with vehicles were studied. In-depth interviews with 18 pedestrians were conducted and cognitive maps were depicted for each of them. 11 of the 18 participants ascribed the crashes at least in part to their own self-regulation failures. The need to motivate elderly pedestrians to respect and adhere to their own highly personal self-regulation is discussed. Abstract: The present study aims to identify, study, and develop typologies based on cases of elderly pedestrian collisions with vehicles where the pedestrians subjectively ascribe the collision at least in part to their own self-regulation failures. Semistructured interview surveys were conducted with 18 elderly people who had experienced a crash with a vehicle as a pedestrian aged 65 years or older. Personal construct theory is adopted as the theoretical underpinning, and it is assumed that pedestrians have their own subjective ways of making sense of the crashes they are involved in. It was found that 11 of the 18 participants ascribed the crashes at least in part to their own self-regulation failures. Cognitive maps of the 11 participants had a common structure, and the associated 11 incidents were classified with respect to the following dimensions: (a) self-regulation type, (b) self-regulation motivation, (c) cause of self-regulation failure, and (d) characteristics of the collisions that occurred after the self-regulation failure. Based on these findings, practical implications are found, and corresponding interventions that may reduce elderly pedestrian–vehicle crashes of this type are discussed. Specifically, this study demonstrates the necessity of education or other intervention that goes beyond informing elderly pedestrians of what is right and wrong in traffic environments. Another critical result—the need to motivate elderly pedestrians to respect and adhere to their own highly personal self-regulation, even if it is not against the social norms—is also presented and discussed.